Anterior Subcutaneous Internal Pelvic Fixation (Anterior Infix) in Management of Pelvic Ring Fractures - Abdallah Ismail, Ahmad Mohammad; Said, Mahmoud Mabrouk; Hassan, Yaser Al-Sayed (Journal of Neonatal Surgery, 2025)
Background: Hemodynamic instability and a high mortality rate are symptoms of pelvic injuries. Reducing mortality, improving fracture reduction, allowing early weight bearing, and mobility are all benefits of surgical fixation for unstable pelvic injuries. Reduced soft tissue injury, less blood loss, shorter operation time, and early postoperative mobilization are all benefits of anterior infix. The aim of the work: was in order to evaluate the clinical, radiological, and postoperative outcomes of anterior INFIX, a method for fixing pelvic rings, as well as any issues that may have occurred during or after the procedure. Patients and methods: Patients who are suitable for anterior fixation through anterior pelvic infix were included in this prospective study. The patients included 30 individuals from the Orthopedic Surgery Department at Al-Zahraa University Hospital and the Faculty of Medicine for Girls at Al-Azhar University. In this study the mean age of the studied cases ranges from 19 to 85 years old with a mean 36.97 years old. All patient's injuries have been resulted from high energy trauma. 10 patients (33.3%) have a lateral compression type 2 injury, 10 patients (33.3%) have vertical shear injury, 9 patients (30%) have a combined mechanism injury, and 1 patient (3.3%) have lateral compression type 3 injury. Results: The mean of operative delay was 11.83 days with a range from 2 to 40 days and Intraoperative blood loss ranged from 30 to 80 milliliter, with an average of 49 milliliter. From all patients, there 27 patients (90%) had posterior fixation in addition to anterior infix. Regarding reduction evaluation (Matta radiological score) 12 patients (40%) were excellent, 15 patients (50%) were good, and 3 patients (10%) were fair. Postoperative lateral femoral cutaneous nerve (LFCN) was found intact in 21 patients (70%) and was injured in 9 patients (30%). From all patients there 2 patients only (6.7%) were have surgical site infection. There was neither fixation failure nor screw loosening in any patient. The mean time for union was 10.87 weeks with a range from 8 to 14 weeks and the mean time for removal was 4.96 months with a range 3 to 12 months. The mean functional score (Majeed score) was 92.5 with a range from 69 to 100. Grading the functional outcome according to Majeed score, 22 patients (73.3%) were excellent, 7 patients (23.3%) were good, and 1 patient (3.3%) was fair. Conclusion: For the treatment of unstable pelvic ring injuries, the INFIX is effective enough. We think this is the gold standard for treating pelvic ring injuries. When external fixation is not an option, the INFIX is a better choice for anterior pelvic fixation. Both the total axial stiffness and the stiffness at the pubic symphysis were higher with INFIX compared to external fixation. Reduced infection risk, more patient mobility, and decreased nursing needs are some of the benefits of the INFIX versus external fixation.